Contribution of potential clean trucks in carbon peak pathway of road freight based on scenario analysis: A case study of China. (15th December 2022) - Zhang, Xizhao; Hao, Xu; Liu, Yang; Wu, Rui; Shan, Xiaonian; Li, Shunxi
Abstract: Reducing the carbon emissions from trucks is critical to achieving the carbon peak of road freight. Based on the prediction of truck population and well-to-wheel (WTW) emission analysis of traditional diesel trucks and potential clean trucks including natural gas, battery-electric, plug-in hybrid electric, and hydrogen fuel cell, the paper analyzed the total greenhouse gas (GHG) emissions of China's road freight under four scenarios, including baseline, policy facilitation (PF), technology breakthrough (TB), and PF-TB. The truck population from 2021 to 2035 is predicted based on regression analysis by selecting the data from 2002 to 2020 of the main variables, such as the GDP scale, road freight turnover, road freight volume, and the number of trucks. The study forecasts the truck population of different segments, such as mini-duty trucks (MiDT), light-duty trucks (LDT), medium-duty trucks (MDT), and heavy-duty trucks (HDT). Relevant WTW emissions data are collected and adopted based on the popular truck in China's market, PHEVs have better emission intensity, especially in the HDT field, which reduces by 51% compared with ICEVs. Results show that the scenario of TB and PF-TB can reach the carbon peak with 0.13% and 1.5% total GHG emissions reduction per year. In contrast, the baseline and PF scenario fail the carbon peak due to only focusing on the number of clean trucks while lacking the restrictions on the GHG emission factors of energy and ignoring the improvement of trucks' energy efficiency, and the total emissions increased by 29.76% and 16.69% respectively compared with 2020. As the insights, adopting clean trucks has an important but limited effect, which should coordinate with the transition to low carbon energy, and the melioration of clean trucks to reach the carbon peak of road freight in China. Graphical abstract: Image 1 Highlights: Scenario analysis is conducted on the carbon peak pathway of China's road freight. Heavy-duty trucks contribute the vast majority of GHG emissions. The TB and PF-TB scenarios can effectively reduce and reach a carbon peak by 2030. The carbon abatement target cannot be achieved only by promoting clean trucks.